Origin and Evolution of Geofluids in the Eocene Red-Bed Sandstones of the Dongying Depression, China: Constraints from Fluid Inclusions in Authigenic Minerals - Wang, Jian; Xie, Mingfeng; Costanzo, Alessandra; Feely, Martin; Cao, Yingchang; Liu, Keyu (Global Journal of Earth Science and Engineering, 2022)
Fluid inclusion and petrographic study focused on authigenic quartz, annealed microfractures in quartz grains (AMF) and carbonate cement, was performed in red-bed reservoir sandstones from the first member of the Kongdian Formation and the lower fourth member of the Shahejie Formation (Shengli oilfield, East China). Both hydrocarbon and aqueous inclusions are present. Microthermometry and Laser Raman spectroscopes of liquid-rich two-phase inclusions showed that the pressure-correction value of aqueous inclusions is < 15°C. Differences in homogenization temperature and salinity occur between inclusions in quartz and carbonate cements. The liquid-rich two-phase aqueous inclusions were classified into four groups based on the salinity-homogenization temperature plots. The liquid-rich two-phase hydrocarbon inclusions were classified into two groups. The timing of the first-stage diagenetic fluid was before 31.3Ma. Fluids were from syn-depositional water and diagenetic fluids of clay minerals in interbedded mudstones. The timing of the second-stage diagenetic fluid was between 31.3 and 26.4Ma. Fluids were rich in organic acids and were accompanied by filling of small amounts of low maturity oil. The timing of the third-stage diagenetic fluid was between 26.4 and 21.4Ma. Fluids were mainly influenced by dehydration of gypsum-salt rocks and decarboxylation of organic acids. The timing of the fourth-stage diagenetic fluid was after 21.4 Ma. Fluids were influenced by organic acids and carbon acids and were accompanied by filling of mature oil after 10Ma. During the burial history, the red-bed reservoirs experienced the evolution process of early alkaline diagenetic fluids, early acid diagenetic fluids, late alkaline diagenetic fluids and late acid diagenetic fluids, which caused the alternate evolution of multiple alkaline and acid diagenetic environments.